Epilepsy and Mood Disorders - Sermin Kesebir; Sertac Guven; Ismail Koc (Psikiyatride Güncel Yaklaşımlar, 2012)
Mood disorders are the most common psychiatric comorbid disorder that affects quality of life and prognosis in epilepsy. The relation between depression and epilepsy is bidirectional. Not only the risk of having a depression among epilepsy cases is more than the healthy control cases, but also the risk of having epilepsy among depressive cases is more than the healthy control cases. People diagnosed with epilepsy are five times more likely than their peers to commit suicide. Moreover it seems that some epilepsy types like temporal lobe epilepsy have a much higher risk (25 times) for suicide. Risk of suicide in epilepsy, which is independent from depression, increases more with the presence of depression. The common pathway between epilepsy, depression and suicide is hypofrontality and irregularity of serotonin metabolism. Contrary to depression, data on relationship between bipolar disorder and epilepsy is limited. However, mood disorder, mixed episodes with irritable character and mania are more frequent than assumed. As a matter of fact, both disorders share some common features. Both are episodic and can become chronic. Kindling phenomenon, irregularities in neurotransmitters, irregularities in voltage gate ion channels and irregularities in secondary messenger systems are variables that are presented in the etiologies of both disorders. Anticonvulsant drugs with mood regulatory effects are the common points of treatment. Understanding their mechanisms of action will clarify the pathophysiological processes. In this article, the relationhip between epilepsy and mood disorders, comorbidity, secondary states and treatment options in both cases have been discussed.